Strategi Perbaikan Kualitas Pelayanan Menggunakan Metoda SERVQUAL dan Model Importance Performance Analysis (IPA) pada Bisnis Kuliner Baso Aci Sambel Garut : Penelitian - Mia Sumiarsih; Ilman Ansori; Nijar Kurnia Romdoni; Putri Kamelia; Ai Rahmatika (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
In the culinary business, service quality is one of the main factors that determine success. Baso Aci Sambel Garut is one of the famous culinary businesses in the Tasikmalaya area. The purpose of this study was to determine the level of gap between consumer expectations and perceptions of the quality of service provided by the culinary business Baso Aci Sambel Garut based on the SERVQUAL dimension. to determine the priority of service quality improvement using the Importance Performance Analysis (IPA) model, and provide service quality improvement strategies to increase customer satisfaction. This study used a descriptive quantitative method. The population in this study were all consumers of baso aci sambel garut. The sampling technique was carried out using convenience sampling. The determination of the number of samples used the Limeshow formula of 100 people. The analysis in this study used Gap Measurement with the SERVQUAL Method, Priority Mapping with Importance Performance Analysis (IPA), and Formulation of Service Quality Improvement Strategies. The results of this study are on the Tangibles dimension (Physical Evidence), Reliability, Responsiveness, and Empathy are indicators with a negative gap level indicating that the quality of service is still not in accordance with consumer expectations. The improvement strategy focuses on Quadrant I of the IPA quadrant diagram which consists of: Employee appearance must be neater and more professional, food is served at the appropriate time, Operating hours must be appropriate, consumers are given clear information about the waiting time for orders, Staff must be quicker to handle errors in orders, employees understand consumer needs and preferences, staff must be willing to help customers with special difficulties, provide food options that suit various customer preferences, and employees must continue to provide good service even when crowded.